Implementation of Religious Moderation at Wahid Hasyim University - Ulumuddin, Imam Khoirul; Shobirin, Ma'as; Martin, Ali; Cholid, Nur; Saefudin, Ahmad (Islamic Review: Jurnal Riset dan Kajian Keislaman, 2024)
Higher Education (PT) as a provider of higher education has an important role in efforts to implement religious moderation, unfortunately, in recent years universities have become fertile fields for regeneration of groups that seek to undermine the existence of the Unitary State of the Republic of Indonesia (NKRI). In its implementation, the Ministry of Religious Affairs established a Moderation House in PTKIN, while in PTU there has been no special attention related to this. In particular, this study aims to find out the concept of implementing diverse moderation in Unwahas, which is a PTU under the auspices of the Ministry of Education and Culture of Research and Technology. This research is a qualitative research using data collection including documents, interviews, and observations. This study found that the implementation of religious moderation at Wahid Hasyim University was carried out in at least two strategic steps, namely through structured and academic programs. The structured program is a program that has been planned and implemented by the Aswaja Center Management and Young Aswaja Activists, Wahid Hasyim University, while academic means through the curriculum of the General Basic Course (MKDU), implemented in the Semester Learning Plan (RPS) of Islamic Religious Education Courses, to Aswajaan, Pancasila and Citizenship and also Compulsory Curriculum Courses (MKWK).